To complete the input-output table for the function \( f(x) = - (x + 1)^2 + 4 \), we need to evaluate the function for each given value of \( x \).
Step 1: Calculate \( f(x) \) for each \( x \) value.
-
For \( x = -1 \): \[ f(-1) = -(-1 + 1)^2 + 4 = -0 + 4 = 4 \]
-
For \( x = 0 \): \[ f(0) = -(0 + 1)^2 + 4 = -1 + 4 = 3 \]
-
For \( x = 1 \): \[ f(1) = -(1 + 1)^2 + 4 = -4 + 4 = 0 \]
-
For \( x = 2 \): \[ f(2) = -(2 + 1)^2 + 4 = -9 + 4 = -5 \]
Step 2: Summarize the results in a table:
| x | f(x) | |----|------| | -1 | 4 | | 0 | 3 | | 1 | 0 | | 2 | -5 |
Step 3: Identify the largest output.
From the computed values:
- \( f(-1) = 4 \)
- \( f(0) = 3 \)
- \( f(1) = 0 \)
- \( f(2) = -5 \)
The largest output is \( 4 \), which occurs at \( x = -1 \).
Answer: x = -1